Frontispiece: Closed Bipolar Electrode Array for Optical Reporting Reaction‐Coupled Electrochemical Sensing and Imaging. Issue 8 (8th February 2023) - Qin, Xiang; Gao, Jiao; Jin, Hua‐Jiang; Li, Zhong‐Qiu; Xia, Xing‐Hua
Abstract : Herein, a closed bipolar electrode (BPE) array using an electro‐fluorochromism (EFC) or electro‐chemiluminescence (ECL) reaction as the reporting reaction is highlighted and the latest related advances are reviewed. Further methods to improve the spatial resolution of the closed BPE array are also proposed. For more details, see the Review by Z.‐Q. Li, X.‐H. Xia, et al. (DOI: 10.1002/chem.202202687 ).